Effect of cyclic meditation on anxiety and sleep quality in sailors on merchant ships—A quasi-experimental study - Sukesh Paranthatta; Titty George; H. M. Vinaya; P. S. Swathi; Mangesh Pandey; Balaram Pradhan; Natesh Babu; Apar Avinash Saoji (Frontiers in Public Health)
BackgroundSailors undergo anxiety and sleep disturbances due to prolonged journeys and the nature of their work on ships. Earlier studies indicate Cyclic Meditation (CM) being beneficial for managing anxiety and improving sleep quality. Thus, the current study was designed to investigate the effect of CM on anxiety and sleep quality among sailors.Materials and methodsFifty sailors were assigned to experimental (n = 25) and control (n = 25) groups. The experimental group received 45 min of CM, 7 days a week for 3 weeks. Control group continued with their routine activities and were offered CM practice the following 3 weeks. Hamilton Anxiety Scale for anxiety (HAM-A) and the Pittsburg Sleep Quality Index (PSQI) for sleep along with blood pressure and pulse rate were taken at baseline and by the end of 3 weeks. Data were analyzed using Repeated Measures Analysis of Variance (RM ANOVA) for within and between group effects.ResultsSignificant differences were found between the groups following 3 weeks for all the variables. Experimental group demonstrated reduced anxiety (p < 0.001) and improved sleep (p < 0.001) along with improvements in blood pressure and pulse rate. The control group did not show any significant changes following 3 weeks.ConclusionCM could be incorporated as a routine for sailors to manage their anxiety and improve sleep quality during the period on board ships.